(Invited) Enabling Hetero-Integration of III-V and Ge-Based Transistors on Silicon with Ultra-Thin Buffers Formed by Interfacial Misfit Technique. (18th August 2016) - Gong, Xiao; Yadav, Sachin; Goh, Kian Hui; Tan, Kian Hua; Kumar, Annie; Low, Kian Lu; Jia, Bowen; Yoon, Soon-Fatt; Liang, Gengchiau; Yeo, Yee-Chia
Abstract : In this paper, we discuss the application of the interfacial misfit (IMF) technique to enable the heterogeneous integration of III-V and Ge-based transistors on Si substrates. Ge pFETs and InAs nFETs were co-integrated on a Si substrate using common contact formation, digital etch, and gate stack formation modules. In addition, vertically stacked nanowire (NW) GaSb pFETs and InAs nFETs on Si substrates were also realized.